Preparation, characterization, bioactivity and degradation behavior in vitro of copper-doped calcium polyphosphate as a candidate material for bone tissue engineering. Issue 67 (4th September 2017) - Guo, Chengrui; Li, Li; Li, Shuangshuang; Wang, Yaping; Yu, Xixun
Abstract : In this study, copper, as one of the essential trace elements in the human body, was introduced into calcium polyphosphate (CPP) to prepare a novel scaffold in bone tissue engineering: copper-doped calcium polyphosphate (CCPP) scaffolds. Abstract : In this study, copper, as one of the essential trace elements in the human body, was introduced into calcium polyphosphate (CPP) to prepare a novel scaffold in bone tissue engineering: copper-doped calcium polyphosphate (CCPP) scaffolds. This novel scaffold was characterized by XRD, FTIR and SEM. The porosity and mechanical properties of CCPP scaffolds were also investigated. Finally, its bioactivity and degradation behavior in vitro were exploited. The results suggested that low-content copper doping had no significant influence on the structure of CPP. The compressive strength of CCPP with 70% porosity was 5–9 MPa which met the strength requirements of cancellous bone (2–12 MPa). The results of degradation experiments from the weight loss of scaffolds and the release of ions obtained from ICP-OES showed that both the incorporation of copper and acidic metabolites from osteoblasts could promote the degradation of CCPP scaffolds. The amount of Cu 2+, Ca 2+ and PO4 3− released from various scaffolds in osteoblast-mediated degradation might be used to elucidate the cytocompatibility of CCPP scaffolds with HUVECs/osteoblasts. MTT assay showed that 0.05% CCPP scaffolds showed a good cytocompatibility with HUVECs/osteoblasts. The ELISA assay showed that 0.05% CCPP scaffolds could promote the secretion of VEGF, ALP and OCN from osteoblasts as well as VEGF from HUVECs, which indicated its good ability to stimulate osteogenesis and angiogenesis. According to the chemical composition and structure of 0.05% CCPP scaffolds, we inferred that 0.05% CCPP scaffolds showed better cytocompatibility and ability to stimulate osteogenesis and angiogenesis due to the synergy effects of copper and the energy produced by the breakage of P\O\P bonds between [PO3 − ] units in CCPP compared with CPP scaffolds and other Cu-containing biomaterials such as copper-doped hydroxyapatite. The results obtained in our study suggest that 0.05% CCPP scaffold is a promising biomaterial for bone repairing applications.